Multimedia computing - Friedland, Gerald, 1978-; Jain, Ramesh, 1949- (Cambridge University Press, 2014)
"The word 'multimedia' is often associated with specific applications from entertainment to web design to video to music. This innovative textbook presents emerging techniques in multimedia computing from an experiential perspective in which each medium - audio, images, text, and so on--is a strong component of the complete, integrated exchange of information or experience. The goal of this book is to present current techniques in computing and communication that will lead to the development of a unified and holistic approach to computing using heterogeneous data sources. The authors introduce the fundamentals of multimedia computing, describing the properties of perceptually encoded information, presenting common algorithms and concepts for handling it, and outlining the typical requirements for emerging applications that use multifarious information sources. Designed for advanced undergraduate and beginning graduate courses, the book will also serve as an introduction for engineers and researchers interested in understanding the elements of multimedia and their role in building specific applications"--Resumé vydavatele
Keywords: multimediální systémy; multimedia systems; učebnice; textbooks